Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1097/md.0000000000011396
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes and prognostic markers in gallbladder cancer

Abstract: Cancer-related inflammation and systemic inflammatory markers have been widely recognized as an essential part in tumor multiplication, invasion, and metastasis of tumor cells. This study aimed to estimate and compare the prognostic value of various biomarkers on overall survival (OS) in patients with gallbladder cancer patients.We performed a retrospective study of 159 patients received different therapies in West China Hospital from 2009 to 2014. The preoperative biomarker data, including neutrophil–lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Previous studies have assessed the effect of serum levels of tumor markers (AFP, CEA, CA19-9, CA72-4, TPA and TK), on prognosis of carcinoma gall bladder and found that TK, TPS and CEA were the independent prognostic factors forOS in GBC. [ 15 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have assessed the effect of serum levels of tumor markers (AFP, CEA, CA19-9, CA72-4, TPA and TK), on prognosis of carcinoma gall bladder and found that TK, TPS and CEA were the independent prognostic factors forOS in GBC. [ 15 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore in one study neutrophil to lymphocyte ratio and CEA were associated with poor OS of GBC patients. [ 16 ] Lee = al assessed CEA and CA 19-9 levels post chemotherapy and found CA 19-9 as the independent and most valuable prognosticator. [ 17 ] Similar findings have been reported by Yu et al , who studied CA 19-9 and CEA as the independent prognostic markers in resectable GBC.…”
Section: Discussionmentioning
confidence: 99%
“…Also, since the outcome for advanced GBC is poor, the willingness of patients with cancer at stage IV for aggressive therapy is usually wobbly, which may impact the strategic choice for surgery to a large extent. On the other hand, the surveyed sample size was limited; the long-term survival come for GBC could be affected by composite factors [6,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Cox proportional hazards model was used for multivariate analysis. The factors identified as significant in univariate analysis were included for the multivariate Cox analysis ( 37 ). Hazard ratios (HRs) were shown as relative risks, with corresponding 95% confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%